2017
DOI: 10.1021/acs.jnatprod.6b01146
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Diverse Alkaloids from the Seeds of Peganum harmala

Abstract: Investigation of the alkaloids from Peganum harmala seeds yielded two pairs of unique racemic pyrroloindole alkaloids, (±)-peganines A–B (1–2); two rare thiazole derivatives, peganumals A–B (3–4); six new β-carboline alkaloids, pegaharmines F–K (5–10); and 12 known analogues. Their structures, including stereochemistry, were elucidated through spectroscopic analyses, quantum chemistry calculations, and single-crystal X-ray diffraction. Notably, the incorporation of pyrrole and indole moieties in peganines A–B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Purification of the residue via flash column chromatography (EtOAc:n-hexane = 1:1) afforded peganumal A (1; 5.4 mg, 89%) as a white solid. The NMR spectra data were consistent with the previously reported [4]. HRMS (FAB) calcd for C 12 H 14 NO 3 S + (M + H + ): 252.0689; found 252.0695; 1 H NMR (500 MHz, DMSO) δ 8.91 (1H, d, J = 0.6 Hz), 8.21 (1H, s), 7.70 (1H, d, J = 0.6 Hz), 6.52 (1H, s), 6.52 (1H, s), 4.08 (2H, s), 3.71 (3H, s), 3.71 (3H, s); 13 C NMR (125 MHz, DMSO) δ 153.1, 148.0, 148.0, 140.5, 139.4, 134.2, 130, 105.9, 105.9, 56.0, 56.0, 31.9.…”
Section: Peganumal a (1)supporting
confidence: 91%
See 3 more Smart Citations
“…Purification of the residue via flash column chromatography (EtOAc:n-hexane = 1:1) afforded peganumal A (1; 5.4 mg, 89%) as a white solid. The NMR spectra data were consistent with the previously reported [4]. HRMS (FAB) calcd for C 12 H 14 NO 3 S + (M + H + ): 252.0689; found 252.0695; 1 H NMR (500 MHz, DMSO) δ 8.91 (1H, d, J = 0.6 Hz), 8.21 (1H, s), 7.70 (1H, d, J = 0.6 Hz), 6.52 (1H, s), 6.52 (1H, s), 4.08 (2H, s), 3.71 (3H, s), 3.71 (3H, s); 13 C NMR (125 MHz, DMSO) δ 153.1, 148.0, 148.0, 140.5, 139.4, 134.2, 130, 105.9, 105.9, 56.0, 56.0, 31.9.…”
Section: Peganumal a (1)supporting
confidence: 91%
“…According to the synthetic procedure of peganumal A (1), peganumal B (2; 88 mg, 69%) was obtained as a white solid from 11 (176 mg, 0.50 mmol) by using 1 M solution of titanium tetrachloride in methylene chloride (0.75 mL, 0.75 mmol). The NMR spectra data were consistent with the previously reported [4]…”
Section: Peganumal B (2)supporting
confidence: 91%
See 2 more Smart Citations
“…Muhaisen et al [24] observed the in vitro antibacterial (Bacillus cereus ATCC 11778, B. subtilis ATCC 6633, Enterococcus faecalis ATCC 29212, E. coli ATCC 25922, P. aeruginosa Wang et al [18] extracted the seeds of P. harmala with ethanol reflux, adjusted the pH of the extract, extracted it, and passed it through the silica gel column. Six new βCs were identified, i.e., pegaharmines F-K (3-8) (Figure 2).…”
Section: Antibacterial Activitymentioning
confidence: 99%